Hizb Ut-Tahrir's Tabanni Concept: the Problem of Internal Unity and External Weakness - Heriansyah Heriansyah; Muhammad Syaroni Rofii (Politicon : Jurnal Ilmu Politik, 2023)
This article explains the tabanni (adoption) concept adopted by Hizbut Tahrir and its relationship with the level of public acceptance of Hizbut Tahrir's ideas, thoughts and ideals. Using a qualitative method through a content analysis approach to the comments of Muslim figures from mainstream organizations, observation and literature study, reinforced by data on the level of public support for Hizbut Tahrir in Indonesia (HTI) from several survey institutions, the author finds that HTI activists failed to socialize their ideas, thoughts and ideals because they lost the test in the public sphere in Habermas' perspective. This is evidenced by public support to the government for the revocation of HTI's legal entity. This failure was caused by the concept of tabanni that they adopted in order to maintain internal unity which had a negative impact on the interaction of HTI activists with external parties. The concept of institutionalized tabanni is pseudo, unable to prevent the internal conflict and frictions that often occur as a result of the party organizational model with single leadership pattern which is semi-military in nature.